PEMETAAN RISET GLOBAL TENTANG PAJAK DIGITAL: ANALISIS BIBLIOMETRIK BERDASARKAN DATA SCOPUS - Sulastri, Sulastri; Santoso, Rachmat Agus; Fitriana, Fitriana (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The development of the digital economy has led to the emergence of an urgency to design a new taxation approach that can accommodate digital economy activities reasonably and effectively, thus giving rise to the concept of digital tax. This research aims to map the global literature related to digital taxation, identify key topics, and find novel opportunities for future research. Methods: The method used was a bibliometric analysis with the VOSviewer application on 49 Scopus-indexed articles for 2018–2025. Results: The mapping results show that the theme of "tax system" is still limited, opening up development opportunities by exploring new keywords, especially in geographical or institutional contexts such as the tax system in developing countries. The co-occurrence analysis produced six clusters with the interesting finding that there is an indirect relationship between tax avoidance and digital taxation. This phenomenon suggests that tax avoidance in the digital economy is more due to structural changes and global responses, such as the BEPS initiative, than digital tax policies. These findings can provide direction for future research in developing digital taxation literature. Keywords: Digital Tax, Digital Taxation, Tax Avoidance, Vosviewer, Scopus